Analyzing the Legal Implications of the Open Proportional System in Indonesian Legislative Elections: A Focus on Political Liberalization and Corruption - Hannan, Abd (Universitas Islam Negeri Walisongo Semarang, 2023)
The study focuses on discussing the problem of legal implementing an open proportional election system in legislative elections in Indonesia, its role and influence on the emergence of political anomalies within the parliament, in this case political liberalization and corruption. The study question is about the dynamics of implementing an open proportional system in the context of elections and how the legislative elections are correlated with the practice of political liberalization and corruption in Indonesia. This study is qualitative research conducted using a library approach. As a result, elections with an open proportional system contain several weaknesses and deficiencies that have the potential to give rise to corrupt practices within the board, both at the regional central level. The potential for the emergence of corrupt practices in open proportional system elections is caused by two things; First, open proportional electoral systems tend to be liberal and capitalist. Competition for leadership tends to focus on pragmatic areas that are centered on money and power relations, no longer in productive areas such as ideas, thoughts, ideas. Second, because of these liberalization and capitalization practices, political costs and expenses soared beyond rational and reasonable limits. In the end, uncontrolled political costs become a financial burden later that they must pay off and return.Studi fokus membahas problem implikasi hukum sistem proporsional terbuka dalam pemilu legislatif di Indonesia, peran dan pengaruhnya terhadap munculnya anomali politik di kalangan dewan, dalam hal ini adalah liberalisasi politik dan korupsi. Pertanyaan kajian adalah dinamika penerapan sistem proporsional terbuka dalam konteks Pemilu serta bagaimana korelasi dalam pemilu legislatif dengan praktik liberalisasi politik dan korupsi di Indonesia. Studi ini merupakan penelitian kualitatif yang dilakukan dengan pendekatan kepustakaan. Hasilnya, gelaran pemilu dengan sistem proporsional terbuka memuat sejumlah kelemahan dan kekurangan yang berpotensi besar menimbulkan praktik korupsi di kalangan dewan, baik di tingkat pusat daerah. Potensi munculnya praktik korupsi dalam pemilu sistem proporsional terbuka disebabkan oleh dua hal; pertama, sistem pemilu proporsional terbuka cenderung liberal dan kapitalis. Kompetisi kepemimpinan cenderung berkutat di wilayah-wilayah prgamatis yang berpusat pada uang dan relasi kekuasaan, bukan lagi ada di wilayah-wilayah produktif semisal ide, pemikiran, gagasan. Kedua, akibat dari praktik liberalisasi dan kapitalisasi tersebut, ongkos dan biaya politik melambung tinggi melebihi batas rasional dan kewajaran. Pada akhirnya, biaya politik tidak terkontrol menjadi beban finansial di kemudian hari yang harus mereka lunasi dan kembalikan.